Results Of The Study Of The Immunotropic Action Of Cyclosiversioside A In Comparison With Immunal In Normal Conditions And In Secondary Immunodeficiency Conditions (Journal of Pharmaceutical Negative Results, 2023)
Cycloartan glycoside cyclosiversioside A, isolated from Astragalus schahrudensis Bunge, when administered orally to mice (10 mg / kg) simultaneously with their immunization with thymus-dependent antigen – sheep erythrocytes (intraperitoneal at a dose of 2 × 107 / mouse) significantly stimulates the process of forming the primary antibody cells, secreting IgM in the spleen of mice.Along with this, cyclosiversioside A increases the total cellularity of the central and peripheral organs of immunity, stimulates erythro- and leukopoiesis. All these changes are reliably expressed not only in normal mice, but also in mice with secondary immunodeficiency states, caused by damage to the liver by carbon tetrachloride, or by their total radioactive irradiation. Cyclosiversioside A has a stimulating effect on immunogenesis to a much greater extent than a preparation with immunostimulating activity – immunal.